Moringa oleifera Lam. leaves prevent Cyclophosphamide-induced micronucleus and DNA damage in mice - Sathya T.N.,; Aadarsh P.,; Deepa V.,; Balakrishna Murthy P., (International Journal of Phytomedicine, 2010)
Chemoprotective effect of ethanolic extract of Moringa oleifera Lam leaves was evaluated on cyclophosphamide (CP)-induced genotoxicity in the mouse. Animals were pre-treated with the extract for seven consecutive days at doses of 250, 500, 1000 and 2000 mg/kg b.w. Micronucleus in bone marrow and comet (DNA damage) in the liver were performed. Cyclophosphamide was administered intra-peritoneally on day 7 and Mice were sacrificed after 24 hours. In CP treated animals, statistically significant induction of micronuclei in polychromatic erythrocytes (PCE) was recorded. However, in the animals pre-treated with the extract, the percentage of CP-induced MN decreased with increasing concentration of the extract. Results of comet assay showed similar decrease in DNA damage in mice pre-dosed with the extract. These results point out to the presence of chemopreventive phytoconstituents in the crude extract offering protection against CP-induced genotoxicity in the mouse.